A preliminary technical study on sodium dodecyl sulfate-induced changes of the nano-structural and macro-mechanical properties in human iliotibial tract specimens. (August 2016) - Hammer, Niels; Huster, Daniel; Boldt, Andreas; Hädrich, Carsten; Koch, Holger; Möbius, Robert; Schulze-Tanzil, Gundula; Scheidt, Holger A
Abstract: Introduction: Acellular scaffolds are frequently used for the surgical repair of ligaments and tendons. Even though data on the macro-mechanical properties related to the acellularization process exist, corresponding data on the nano-structural properties are still lacking. Such data would help identify target proteins of the formed extracellular matrix that are chemically altered by the acellularization. In this study we examined the altered structure by comparing molecular properties of collagens from native and acellular iliotibial tract samples to the macroscopic stress–strain behavior of tract samples. Material and methods: Matched pairs of five human iliotibial tract samples were obtained from five donors (mean age 28.2±4.7 years). One of each pair was acellularized using 1 vol% sodium dodecyl sulfate (SDS) for 7 days. 13 C magic angle spinning nuclear magnetic resonance spectroscopy ( 13 C CP MAS NMR) was utilized to compare the collagen overall secondary structure and internal dynamics of collagen-typical amino acid proteins. The resulting data was compared to age-matched stress–strain data of tract samples obtained in an uniaxial tensile setup and histologically. Results: Typical and nearly identical collagen 13 C CP MAS NMR spectra were found in the tract samples before and after acellularization with SDS. The characteristic collagen backbone remained intact in the native and acellular samples. Collagen molecular composition was largely unaltered in both conditions. Furthermore, a similar dynamic behavior was found for the amino acids Hyp γ, Pro α/Hyp α, Ala α, Gly α and Ala β. These minute alterations in the collagens' molecular properties related to acellularization with SDS were in line with the similarly minute changes in the macro-mechanical tensile behavior, such as the elastic modulus and ultimate stress. Histology showed intact type I collagens, minute amounts of elastins before and after acellularization and evidence for acellularization-induced reductions of proteoglycans. Discussion: Nano-structural properties of collagens are minutely affected by SDS treatment for acellularization, indicated by the molecular composition and dynamics. The lacking acellularization-related changes in the molecular structure properties of collagens in iliotibial tract samples are in line with the small alterations in their macro-mechanical tensile behavior. Though the given setup approaches soft tissue mechanics from both scaling extremes of mechanical testing, further structural analyzes are needed in a larger sample size to substantiate these findings. Highlights: Native and acellular iliotibial tracts were tested nano-structurally and mechanically. 13 C CP MAS NMR was used to compare collagen secondary structure and internal dynamics. Nano-structural dynamics of collagens are hardly altered in acellular scaffolds. Minute changes observed in 13 C CP MAS NMR resemble the tensile behavior of tract